ISO 9001 Quality Management Systems: Literature review - Saraiva, M.; Novas, J. C.; Ferreira, O.; Pires, A. R. (TMQ - Techniques, Methodologies and Quality, 2017)
This paper is focused on the state of the art in regards to the motivations, benefits and difficulties of implementation and certification of quality management systems (QMS) in organizations. The literature review suggests that, in regard to internal or external motives, some may be more or less intense than others, depending on the type of organization and its operating context. As a general rule literature points out to a better performance of organizations that have a QMS according to ISO 9001, although some studies have shown that correlation between the QMS certification and performance is only marginal, or does not exist. On the other hand, the greatest difficulties in implementation and certification of QMS are felt in the bureaucracy, weak commitment to quality, cost and time spent. Finally, we raise methodological questions about research on these topics, and other dimensions of analysis are recommended.